Guideline for radioimmunotherapy of rituximab relapsed or refractory CD20+ follicular B-cell nonHodgkin´s lymphoma - Fischer, M.; Behr, T.; Grünwald, F.; Knapp, W. H.; Trümper, L.; von Schilling, C.; für die Deutsche Gesellschaft für Nuklearmedizin; Schilling für die Deutsche Gesellschaft für Hämatologie und Onkologie (Nuklearmedizin - NuclearMedicine, 2004)
This guideline is a prerequisite for the quality management in the treatment of non-Hodgkin-lymphomas using radioimmunotherapy. It is based on an interdisciplinary consensus and contains background information and definitions as well as specified indications and detailed contraindications of treatment. Essential topics are the requirements for institutions performing the therapy. For instance, presence of an expert for medical physics, intense cooperation with all colleagues committed to treatment of lymphomas, and a certificate of instruction in radiochemical labelling and quality control are required. Furthermore, it is specified which patient data have to be available prior to performance of therapy and how the treatment has to be carried out technically. Here, quality control and documentation of labelling are of greatest importance. After treatment, clinical quality control is mandatory (work-up of therapy data and follow-up of patients). Essential elements of follow-up are specified in detail. The complete treatment inclusive after-care has to be realised in close cooperation with those colleagues (haematology-oncology) who propose, in general, radioimmunotherapy under consideration of the development of the disease.
Keywords: Radioimmunotherapy; non-Hodgkin-lymphoma; CD20-receptors; Zevalin; Yttrium-90